Konstelasi Kekuatan Politik Lokal Dalam Pilkada Gubernur Jambi 2024: Studi Kasus Dari Perspektif Teori Elite - Nasuhaidi Nasuhaidi; M Wira Anshori; Alva Beriansyah (LPPM Universitas Abdurrab, 2025)
This study examines the dynamics of electoral contestation in the 2024 Gubernatorial Election of Jambi Province, focusing on the interaction between formal and informal political forces. The main issue addressed is the lack of a comprehensive understanding regarding the strategic role of the Jambi Malay Customary Institution and the contribution of local elite actors both formal and informal in influencing the election outcome. The objective of this research is to identify and analyze the contribution of local power in determining the direction of electoral political contestation. Employing a qualitative approach with a case study design and elements of narrative research, data were collected through in-depth interviews, document analysis, and field observations. The findings reveal that informal elites such as traditional leaders, religious figures, businesspeople, and former officials possess moral authority and strong patronage networks. Meanwhile, the Malay Customary Institution and ethnic associations function as channels for mobilization based on primordial ties. On the other hand, political parties, local media, and social media play a role in disseminating information and shaping public opinion. The Jambi election reflects a hybrid political landscape in which informal power and formal structures are deeply intertwined. Theoretically, this study enriches local political discourse by highlighting the importance of informal power in electoral democratic practices. Practically, the findings offer strategic insights for candidates, political parties, and election organizers in designing campaign strategies and regulatory approaches that are more adaptive to local power configurations.